Analisis Hukum Islam Terhadap Kebiasaan Transaksi Chip pada Game Domino Online - Alwi, Syamsul Rizal; Wijaya, Abdi; Lewa, Irfan (Universitas Islam Negeri Alauddin Makassar, 2022)
This article aims to describe and analyze the behavior of chip transactions in online domino games, seen from the perspective of Islamic law which is then linked to what happened in Kab. Pangkajene and the Islands. In answering the above problems, the authors took the field research method (Field Research) in this study. To obtain accurate, actual, and reliable information, while the data was obtained through documentation of observations and interviews, which were then analyzed by qualitative descriptive methods. The results of this study indicate that buying and selling chips can be done in 2 ways, first, through the official agent of Higgs Domino Island, and secondly, through fellow gamers who have more chips. Higgs domino island has both positive and negative effects, but the harm it causes outweighs the benefits. This chip buying and selling transaction is illegal and illegal, because the process of getting this chip contains an element of gambling, so the object being traded becomes forbidden.